2016
DOI: 10.1103/physreva.94.022339
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement swapping between dissipative systems

Abstract: In this paper, we investigate the possibility of entanglement swapping between two distinct qubits coupled to their own (in general) non-Markovian environments. This is done via Bell state measurement performing on the photons leaving the dissipative cavities. In the continuation, we introduce the concept of entangling power to measure the average of swapped entanglement over all possible pure initial states. Then, we present our results in two strong and weak coupling regimes and discuss the role of detuning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 41 publications
6
9
0
Order By: Relevance
“…The maximum amount of linear entropy is obtained for θ = 0. For β = 0, we recover the results presented in [62].…”
Section: Atom-field Entanglement Of Subsystemssupporting
confidence: 79%
“…The maximum amount of linear entropy is obtained for θ = 0. For β = 0, we recover the results presented in [62].…”
Section: Atom-field Entanglement Of Subsystemssupporting
confidence: 79%
“…It also has been put forward the idea that, entanglement may be generated between subsystems that never directly interacted by means of entanglement swapping [12]. Recently, it has been reported that the entanglement swapping can also be occurred between dissipative systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…At first, the entanglement can be generally generated by performing interaction [3][4][5][6][7][8][9] or using beam splitter [10,11]. Secondly, this generated entanglement can be swapped (to the separable pairs) using Bell state measurement (BSM) [12][13][14], beam splitter [15] or via performing interaction between independent particles (QED method) [16]. In quantum repeater protocols, after producing entanglement and swapping entanglement between separable parts appropriately, these entangled states are stored in quantum memories.…”
Section: Introductionmentioning
confidence: 99%